2015
DOI: 10.1063/1.4922251
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen defect processes in silicon and silicon germanium

Abstract: Silicon and silicon germanium are the archetypical elemental and alloy semiconductor materials for nanoelectronic, sensor, and photovoltaic applications. The investigation of radiation induced defects involving oxygen, carbon, and intrinsic defects is important for the improvement of devices as these defects can have a deleterious impact on the properties of silicon and silicon germanium. In the present review, we mainly focus on oxygen-related defects and the impact of isovalent doping on their properties in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 184 publications
0
59
0
Order By: Relevance
“…Isovalent doping in Si is technologically important (i.e., photovoltaics) and it can be used to improve the radiation hardness of Si [38]. In particular, it was previously determined that isovalent doping can suppress the formation of oxygen-and carbon-related radiation defects in Si, thus allowing its application in photovoltaics [38].…”
Section: Isovalent Doping In Siliconmentioning
confidence: 99%
“…Isovalent doping in Si is technologically important (i.e., photovoltaics) and it can be used to improve the radiation hardness of Si [38]. In particular, it was previously determined that isovalent doping can suppress the formation of oxygen-and carbon-related radiation defects in Si, thus allowing its application in photovoltaics [38].…”
Section: Isovalent Doping In Siliconmentioning
confidence: 99%
“…In previous investigations it was shown that the introduction of large isovalent dopants such as Sn can impact dopant-defect interactions in Ge (and in Si) [12,19]. In the present study we have employed density functional theory (DFT) modeling to investigate the structure of the C i O i defect in Ge and its interaction with isovalent dopants such as Si or Sn.…”
Section: Introductionmentioning
confidence: 99%
“…For decades the characteristic dimensions of devices were reduced and this has constituted the importance of point defects and defect clusters increasingly important as they can impact materials properties. Examples include the need to reduce the concentration of vacancy-oxygen pairs (VO or A-centers) and/or the carbon-related defects (such as C i O i (Si I ) n , n = 1, 2,…) in Si [13][14][15][16][17][18][19] and the requirement to contain the fast n-type dopant diffusion in Ge [2,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…To optimise devices the control of oxygen-related defects such as the A-center (vacancy-oxygen interstitial pairs, VO) and the carbonrelated defects (such as C i O i (Si I ) n , n = 1, 2,…) is required [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%